# Solve for s (2s)/5-s/3=3 2s5-s3=3
Simplify 2s5-s3.
To write 2s5 as a fraction with a common denominator, multiply by 33.
2s5⋅33-s3=3
To write -s3 as a fraction with a common denominator, multiply by 55.
2s5⋅33-s3⋅55=3
Write each expression with a common denominator of 15, by multiplying each by an appropriate factor of 1.
Multiply 2s5 and 33.
2s⋅35⋅3-s3⋅55=3
Multiply 5 by 3.
2s⋅315-s3⋅55=3
Multiply s3 and 55.
2s⋅315-s⋅53⋅5=3
Multiply 3 by 5.
2s⋅315-s⋅515=3
2s⋅315-s⋅515=3
Combine the numerators over the common denominator.
2s⋅3-s⋅515=3
Simplify the numerator.
Factor s out of 2s⋅3-s⋅5.
Factor s out of 2s⋅3.
s(2⋅3)-s⋅515=3
Factor s out of -s⋅5.
s(2⋅3)+s(-1⋅5)15=3
Factor s out of s(2⋅3)+s(-1⋅5).
s(2⋅3-1⋅5)15=3
s(2⋅3-1⋅5)15=3
Multiply 2 by 3.
s(6-1⋅5)15=3
Multiply -1 by 5.
s(6-5)15=3
Subtract 5 from 6.
s⋅115=3
s⋅115=3
Multiply s by 1.
s15=3
s15=3
Multiply both sides of the equation by 15.
15⋅s15=15⋅3
Simplify both sides of the equation.
Cancel the common factor of 15.
Cancel the common factor.
15⋅s15=15⋅3
Rewrite the expression.
s=15⋅3
s=15⋅3
Multiply 15 by 3.
s=45
s=45
Solve for s (2s)/5-s/3=3

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top